Demonstrating the benefits of a multidisciplinary aerodigestive program. (27th March 2019) - Ruiz, Amanda G.; Bhatt, Jay M.; DeBoer, Emily M.; Friedlander, Joel; Janosy, Norah; Peterson, Melissa Brooks; Wine, Todd; Deterding, Robin; Prager, Jeremy D.
Abstract : Objectives/Hypothesis: The Aerodigestive Program (the Aero Program) at Children's Hospital Colorado is a multidisciplinary program focused on airway, digestive, and lung disorders in complex children, involving collaboration between gastroenterology, pulmonology, anesthesiology, and otolaryngology in clinic and operating room. These programs have proliferated as institutions focus on providing greater care coordination and family satisfaction. However, few cost, charge, and satisfaction data exist to support these resource‐intensive programs. The goal of this study was to investigate the value of combined triple endoscopy delivered by the Aero Program through analysis of institutional charges, direct costs, operating room efficiency metrics, and parent satisfaction. Study Design: Program evaluation. Methods: Finance, satisfaction, efficiency, and quality‐of‐care metrics were evaluated within and outside of the Aero Program through retrospective queries of electronic health records, administrative databases, and parent surveys at our institution. Results: Mean anesthesia time in the Aero Program was 54 minutes (49–60; 95% confidence interval), which was significantly less ( P < .0001) than the estimated 89 minutes of having the three procedures done separately. Average charges and average direct costs for triple endoscopy were 38.8% and 41.9% less than the sum of the averages for separate procedures, respectively. Parent satisfaction was high for the Aero Program care. Conclusions: As organizations move toward greater coordination of care for complex patients, multidisciplinary programs must demonstrate their value by delivering cost‐effective care. Aerodigestive programs have the potential to provide satisfying care that is less costly to the organization, insurer, and family. These programs represent a step in the evolution toward higher value care and value‐based payment methodology. Level of Evidence: 4 Laryngoscope, 130:521–525, 2020